1999
DOI: 10.1093/oxfordjournals.jbchem.a022548
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning of cDNA Encoding a Novel Microphthalmia- Associated Transcription Factor Isoform with a Distinct Amino-Terminus

Abstract: Microphthalmia-associated transcription factor (MITF) is a basic helix-loop-helix-leucine zipper protein, and plays an important role in the development of various cell types, such as neural-crest-derived melanocytes and optic-cup-derived retinal pigment epithelium. Three isoforms of MITF with distinct amino-termini have been described. These include melanocyte lineage-specific MITF-M, heart-type MITF-H, and the recently identified MITF-A. Here we identify a fourth isoform, MITF-C, with a unique amino-terminus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
90
3
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(97 citation statements)
references
References 35 publications
2
90
3
2
Order By: Relevance
“…The above pattern is consistent with (but more complex than) other studies using melanoma cells and the C5 antibody (Bertolotto et al, 1998;King et al, 1999;Wu et al, 2000) or another antibody (D5) in which an B55 -60 kDa Mitf-M doublet is detected. Several considerations indicate that in Mel28 cells, either the fastest migrating polypeptide (indicated by an open box in Figure 3B) or the slower migrating doublet (open circles, Figure 3B) or both of the above, are Mitf-M. First, Mitf-M is significantly smaller than all other Mitf isoforms ( Figure 3A) and migrates faster in SDS gels at around 55 -60 kDa (Fuse et al, 1999). Figure 3B) is consistent with the size of the more widely expressed Mitf-A isoform (Fuse et al, 1999).…”
Section: Expression Of Mitf-m Protein In Ccs Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…The above pattern is consistent with (but more complex than) other studies using melanoma cells and the C5 antibody (Bertolotto et al, 1998;King et al, 1999;Wu et al, 2000) or another antibody (D5) in which an B55 -60 kDa Mitf-M doublet is detected. Several considerations indicate that in Mel28 cells, either the fastest migrating polypeptide (indicated by an open box in Figure 3B) or the slower migrating doublet (open circles, Figure 3B) or both of the above, are Mitf-M. First, Mitf-M is significantly smaller than all other Mitf isoforms ( Figure 3A) and migrates faster in SDS gels at around 55 -60 kDa (Fuse et al, 1999). Figure 3B) is consistent with the size of the more widely expressed Mitf-A isoform (Fuse et al, 1999).…”
Section: Expression Of Mitf-m Protein In Ccs Cellsmentioning
confidence: 99%
“…Several considerations indicate that in Mel28 cells, either the fastest migrating polypeptide (indicated by an open box in Figure 3B) or the slower migrating doublet (open circles, Figure 3B) or both of the above, are Mitf-M. First, Mitf-M is significantly smaller than all other Mitf isoforms ( Figure 3A) and migrates faster in SDS gels at around 55 -60 kDa (Fuse et al, 1999). Figure 3B) is consistent with the size of the more widely expressed Mitf-A isoform (Fuse et al, 1999). Significantly, with respect to the presumptive Mitf-M isoforms in Mel28 cells (open box and/or open circles), the C5 antibody detected a similar but not identical pattern of polypeptides in all CCS cell lines (see discussion).…”
Section: Expression Of Mitf-m Protein In Ccs Cellsmentioning
confidence: 99%
“…Although it was reported that Mitf-A is predominantly expressed in the RPE, this mRNA is ubiquitous like the heart-type, Mitf-H Udono et al, 2000). In addition, in humans, MITF-B, MITF-C, and MITF-D have been isolated Fuse et al, 1999;Takeda et al, 2002); and now MITF-J/Mitf-J have been reported in human and mouse (Hershey and Fisher, 2005 (Kumasaka et al, 2004). In Xenopus, XlMitf␣ is expressed in melanophore lineages, the RPE, and epiphysis, although we could not identify isoform-specific expression (Kumasaka et al, 2004 …”
Section: Introductionmentioning
confidence: 99%
“…7,8 The Mitf consists of at least seven isoforms, referred to as Mitf-M, A, B, C, D, E and H, which differ from each other at their amino-termini corresponding to alternative spliced forms of a single gene. Among them, Mitf-M is specifically expressed in melanocytes and melanomas, 9 while other isoforms are also expressed in retinal pigment epithelium (Mitf-A, B, C, D and H), [10][11][12][13] macrophages (Mitf-A, D and H), 13 mast cells (Mitf-A, D, E and H), 13 as well as other types of cells (Mitf-A, C and H). 13,14 Through binding to the specific recognition motif, that is, the M box sequence (CATGTG), Mitf enhances transcription of the genes encoding major enzymes in the melanin synthesis pathway, including tyrosinase, 15,16 tyrosinase-related protein 1 (TRP-1), 16 TRP-2 11 and dopachrome tautomerase 17 as well as other melanogenic genes, such as SILV/PMEL17/GP100 and MLANA/MART-1.…”
Section: Introductionmentioning
confidence: 99%